2019
DOI: 10.1159/000507329
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>E3</i></b> Gene-Based Genetic Characterization of Canine Adenovirus-2 Isolated from Cases of Canine Gastroenteritis in India Revealed a Novel Group of the Virus

Abstract: Canine adenovirus (CAV) circulates as two distinct serotypes, CAV-1 and CAV-2, which are antigenically related but differ in their clinical manifestations. CAV is one of the important viral agents in the etiology of canine gastroenteritis. Here, we report the molecular surveillance and genetic characterization of CAV from clinical cases of canine gastroenteritis. A total of 302 fecal/rectal swabs were collected from dogs presented with gastroenteritis at various clinics in and around Hyderabad, India during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…2 a). These findings are in agreement with a recent study from India [ 9 ] and reinforce the unique signature “G” nt. insertion in E3 gene of Indian CAV-2 isolates.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2 a). These findings are in agreement with a recent study from India [ 9 ] and reinforce the unique signature “G” nt. insertion in E3 gene of Indian CAV-2 isolates.…”
Section: Resultssupporting
confidence: 93%
“…After the introduction of live-modified vaccines and their widespread use to control disease, the incidence of canine adenoviral infections has reduced [ 20 ] and until a recent study [ 9 ], the prevalence of CAV-2 in the dog population in India was unreported. It is to mention that there are only a few reports of CAV-2-associated neurological disease of dogs and hence, the possibility of CAV-2 causing the nervous signs is ignored by the clinicians which could be the reason that CAV-2 remained unreported in the past.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine parvovirus (CPV) (Caddy 2018), Canine distemper virus (CDV) (Quintero-Gil et al 2019), Canine adenovirus (CAdV) (Ramidi et al 2020), Canine coronavirus (CCoV) (Buonavoglia et al 2006), Canine astrovirus (CaAstV) (Fauquet and Fargette 2005), Canine rotavirus (CRV) (Ortega et al 2017) were frequently reported as a cause for viral gastroenteritis in dogs. CPV belonging to Parvoviridae family is highly contagious and was rst identi ed in dogs suffering from severe hemorrhagic gastroenteritis and myocarditis as CPV-2 variant (Appel et al 1979;Hoang et al 2019); later on replaced by three antigenic variants namely CPV-2a, CPV-2b, and CPV-2c (Zhong et al 2014;Sharma et al 2016;Chiang et al 2016;Zhou et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that at least fteen different lineages of CDV are circulating worldwide (Bhatt et al 2019;Kodi et al 2020). CAdV belongs to Adenoviridae family and circulates as two distinct serotypes, CAdV-1 and CAdV-2 (Mohammadi et al 2011;Ramidi et al 2020). Despite routine vaccinations, re-emergence of CAdV-2 was documented throughout the world (Balboni et al 2014).…”
Section: Introductionmentioning
confidence: 99%